2003
DOI: 10.1614/0043-1745(2003)051[0546:ionado]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Influence of nitrogen and duration of weed interference on corn growth and development

Abstract: An improved understanding of the effects of nitrogen (N) on crop-weed interactions is needed for the development of integrated weed management systems where responsible use of N fertilizers is considered. Field experiments conducted in 1999 and 2000 at two locations in eastern Nebraska quantify the effects of N and increasing duration of weed interference on corn growth and development. A naturally occurring population of weeds was allowed to compete with the corn crop for increasing lengths of time and at thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
55
0
3

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(68 citation statements)
references
References 32 publications
10
55
0
3
Order By: Relevance
“…These findings are similar to those of Evans et al (2003), who reported an increase in PC leaf in weed-free compared to weedy corn. Note.…”
Section: Biomass Production and Partitioningsupporting
confidence: 90%
See 1 more Smart Citation
“…These findings are similar to those of Evans et al (2003), who reported an increase in PC leaf in weed-free compared to weedy corn. Note.…”
Section: Biomass Production and Partitioningsupporting
confidence: 90%
“…It is also important to know how production factors influence the CPWC. Evans et al (2003) reported that the increase in nitrogen level reduced the length of CPWC in corn (Zea mays L.), and narrow row spacing delayed the CTWR in soybean (Knezevic et al 2003a(Knezevic et al , 2003b.…”
mentioning
confidence: 99%
“…), Amaranthus species, and Setaria species at HAL in 1999 and 2000 and at the ARDC in 2000. Pennsylvania smartweed (Polygonum pensylvanicum L.) was an additional dominant weed at the ARDC in 1999 (Evans et al 2003b). …”
Section: Methodsmentioning
confidence: 99%
“…rudis and Abutilon theophrasi Medic. (Evans et al 2003). Results obtained in Iowa have shown that composted swine manure applied at rate of 4000 or 8000 kg C ha -1 reduced the emergence of A. tuberculatus var.…”
Section: Response To Other Human Manipulationsmentioning
confidence: 99%